THE PHENOMENON OF MARRIAGE IS SCARY AMONG GENERATION Z IN BENGKULU CITY - Rodiah April Liani; Panji Suminar; Diyas Widiyarti (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study aims to examine the factors influencing the emergence of the Marriage is Scary phenomenon among young people in Bengkulu City. This phenomenon represents fear toward marriage, which is perceived as a source of emotional, economic, and social burden. Using a descriptive quantitative approach, this study applies structural functionalism theory to understand changes in social values affecting the role of the family institution. This study involved 384 respondents, using purposive sampling technique. Data were collected through online and offline questionnaires distributed to unmarried young individuals who are active on social media and reside in Bengkulu City. The findings indicate that psychological and sociocultural factors play a more dominant role in shaping fear of marriage compared to economic considerations. Mental well-being concerns, the prioritization of career and education, and exposure to social media narratives significantly influence attitudes toward marriage. These results suggest a shift in values among young people toward independence, self-development, and emotional readiness before entering marital life. Policymakers should develop premarital education programs and financial literacy campaigns specifically designed for Generation Z in Bengkulu City.